2015
DOI: 10.1016/j.apgeochem.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Tracing sources of ammonium in reducing groundwater in a well field in Hanoi (Vietnam) by means of stable nitrogen isotope (δ15N) values

Abstract: Tracing sources of ammonium in reducing groundwater in a well field in Hanoi (Vietnam) by means of stable nitrogen isotope (δ15N) values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…While we find at Nam Du that, due to the high infiltration, the kinetically controlled reductive dissolution of As-containing Fe-oxides only contributes insignificantly to the groundwater arsenic content, the study at Van Phuc suggest that the slow infiltration rates allow much-higher arsenic concentrations to build up in the groundwater. 26 An additional reason for the much-higher arsenic concentrations found in porewater of the shoreface sediment could also be that Van Phuc is located just downstream of the channel at Yen My, which drains most of the untreated urban wastewater from the city of Hanoi into the Red River, 24 providing an ample source of reactive carbon.…”
Section: Results and Discussionmentioning
confidence: 99%
“…While we find at Nam Du that, due to the high infiltration, the kinetically controlled reductive dissolution of As-containing Fe-oxides only contributes insignificantly to the groundwater arsenic content, the study at Van Phuc suggest that the slow infiltration rates allow much-higher arsenic concentrations to build up in the groundwater. 26 An additional reason for the much-higher arsenic concentrations found in porewater of the shoreface sediment could also be that Van Phuc is located just downstream of the channel at Yen My, which drains most of the untreated urban wastewater from the city of Hanoi into the Red River, 24 providing an ample source of reactive carbon.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Li et al [52] found that NH 4 -N can deprotonate to ammonia in conditions with a pH value larger than 6, and the ammonia product can degas, particularly with water temperatures in a range of 19-27 • C. In this study, the pH range was from 6.7 to 8.1 in the groundwater. Under such conditions, NH 4 -N is likely to be degassed by a reaction of NH 4 + (aq)-NH 3 (aq)-NH 3 (g) and emitted from the groundwater to the unsaturated pore space [53].…”
Section: Temporal Variations Of Nitrogen and Cod In Groundwatermentioning
confidence: 99%
“…Generally, under aerobic condition, ammonium-nitrogen (NH 4 + -N) concentration in groundwater is <0.2 mg/L, and it may increase more than ten times under anaerobic environment [4]. The considerably high ammonium groundwater concentrations are indications of anthropogenic contamination from sources such as fertilizer, manure, septic tanks, and sewage [4][5][6]; therefore, these undesirable concentrations need to be removed [7,8]. Additionally, previous research found that high concentration of ammonium in groundwater is significantly correlated with high contents of more dangerous contaminants, which are dissolved iron and manganese [9].…”
Section: Introductionmentioning
confidence: 99%